Diaphragm walls & anchorages proceedings of the conference organized by the Institution of Civil Engineers and held in London, 18-20 September 1974 - Darwent, Thelma J. (Institution of Civil Engineers, 1975)
Following an opening address by Sir Kirby Laing, the papers in this book discuss the practical considerations affecting the construction of diaphragm walls, highlight some practical aspects of diaphragm wall construction and conclude with diaphragm wall specification. C. Veder provides the closing address.